Comparative Analysis of Kaba, Al-’Ashri and Al-Bisri Dictionaries (Lexicography Studies) - Anisatu Thoyyibah; Ahmed Mohamed Eltoukhy (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2021)
Dictionaries are one of the means of finding vocabulary, especially in foreign languages. Besides, the dictionary also provides other information related to phonology, syntax, semantics, maps, profiles of a person, and others. Although not all dictionaries collect all the information needed by the user. But with a dictionary, it becomes easier to understand a word. The purpose of this study was to compile Kamus Akbar Bahasa Arab (KABA), Al-'Ashri, and Al-Bisri seen from the point of view of lexicography through comparative scalpels by looking at the aspects of the purpose, content, and shape of the three components of the dictionary. Besides, the author also described the similarities and differences among the three dictionaries. This study used a qualitative descriptive method. This type of research is a library research with research objects were Kamus Akbar Arabic (KABA), Al-'Asri, and Al-Bisri. Data collection used of this study was documentation and recording techniques. The data were analyzed using comparative methods. The results of this study showed that the three dictionaries had their advantages and disadvantages. However, observers or Arabic learners can choose one of these three dictionaries according to their purpose